THERAPEUTIC MANAGEMENT OF ACUTE TRAUMATIC BRAIN INJURY: RESUSCITATION AND NEUROPROTECTION PROTOCOLS (International Seven Journal of Multidisciplinary, 2026)
Moderate to severe traumatic brain injury (TBI) represents a critical global challenge, requiring accurate neuroprognostication to guide triage and decisions regarding withdrawal of life-sustaining therapy. Contemporary management emphasizes multimodal monitoring, in which invasive Intracranial Pressure (ICP) measurement is increasingly supplemented by Brain Tissue Oxygen Pressure (PbtO₂), a crucial marker of tissue hypoxia independently associated with unfavorable outcomes. In parallel, advances in serum biomarkers—particularly glial fibrillary acidic protein (GFAP), neurofilament light chain (NfL), and ubiquitin carboxy-terminal hydrolase L1 (UCH-L1)—allow assessment of injury severity and monitoring of clinical trajectory through minimally invasive methods. Established predictive models such as the IMPACT and CRASH scores demonstrate moderate reliability (with AUC values up to 0.85 for mortality in IMPACT), although the overall quality of evidence is often downgraded due to self-fulfilling prophecy bias and heterogeneity in functional outcome assessment. In the pediatric setting, injury-specific characteristics necessitate greater reliance on advanced Magnetic Resonance Imaging (MRI), in contrast to the predominant use of computed tomography (CT) in adults. The integration of these objective data is essential to guide acute interventions—including ICP management and the judicious use of hyperosmolar therapies—and to inform long-term rehabilitation planning. Predictors such as bilateral absence of pupillary reactivity are considered moderately reliable indicators of in-hospital mortality.